2019
DOI: 10.1001/jama.2018.19802
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Dose Intracoronary Alteplase During Primary Percutaneous Coronary Intervention on Microvascular Obstruction in Patients With Acute Myocardial Infarction

Abstract: IMPORTANCE Microvascular obstruction commonly affects patients with acute ST-segment elevation myocardial infarction (STEMI) and is associated with adverse outcomes. OBJECTIVE To determine whether a therapeutic strategy involving low-dose intracoronary fibrinolytic therapy with alteplase infused early after coronary reperfusion will reduce microvascular obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
3
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(87 citation statements)
references
References 25 publications
0
58
3
2
Order By: Relevance
“…Of interest, when percutaneous coronary intervention (PCI) is not an immediate option, current guidelines on ST-elevated myocardial infarction (STEMI) recommends fibrinolytic therapy with r-tPA [ 25 ]. Yet, a recent trial investigating the use of low-dose r-tPA as an adjunctive therapy to PCI was stopped because of futility [ 26 ], with a post-hoc analysis demonstrating that r-tPA could potentially increase microvascular obstruction in STEMI patients with ischemic time between 4 to 6 h [ 27 ]. As neutrophils play an important role in the pathophysiology of such a complication, we can speculate that r-tPA-mediated neutrophil degranulation and migration might have contributed to the neutral findings of the trial.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, when percutaneous coronary intervention (PCI) is not an immediate option, current guidelines on ST-elevated myocardial infarction (STEMI) recommends fibrinolytic therapy with r-tPA [ 25 ]. Yet, a recent trial investigating the use of low-dose r-tPA as an adjunctive therapy to PCI was stopped because of futility [ 26 ], with a post-hoc analysis demonstrating that r-tPA could potentially increase microvascular obstruction in STEMI patients with ischemic time between 4 to 6 h [ 27 ]. As neutrophils play an important role in the pathophysiology of such a complication, we can speculate that r-tPA-mediated neutrophil degranulation and migration might have contributed to the neutral findings of the trial.…”
Section: Discussionmentioning
confidence: 99%
“…We found that MVO did not differ with alteplase vs. placebo. 2 Here, we report the efficacy and safety of intracoronary alteplase at 1year.…”
Section: Confidential -Under Embargo 1mentioning
confidence: 96%
“…1 Distal embolization and microvascular thrombosis contribute to MVO. In the T-TIME trial (NCT02257294), 2 we hypothesized that low-dose intracoronary fibrinolysis with alteplase, in patients with adequate anticoagulation undergoing primary PCI, would reduce MVO extent as assessed by contrast enhanced cardiovascular magnetic resonance imaging. We found that MVO did not differ with alteplase vs. placebo.…”
Section: Confidential -Under Embargo 1mentioning
confidence: 99%
“…(35) context, full dose intracoronary tenectaplase was inferior to abciximab in a small randomised trial (43) and using low dose intracoronary tenecteplase after reperfusion in the T-time trial also failed to reduce MVO measured using cardiac magnetic resonance imaging (CMRI). (44) Hypothesis generating results were presented by the Microvascular Reperfusion Utilising Sonothrombolysis in Acute Myocardial Infarction (MRUSMI) investigators. (45) Remote preconditioning in STEMI was studied in the CONDI-2/ ERIC PPCI trial, (46) survival remained only significant for high-risk NSTEMI.…”
Section: Optimising Treatment In St-segment Elevation Myocardial Infamentioning
confidence: 99%